The influence of computer screen polarity and color on the accuracy of workers' reading of graphics. - Shih, Yi-Nuo; Huang, Rong-Hwa; Lu, Shih-Feng (Work, 2013)
BACKGROUND: Many professional workers such as engineers and designers must read and comprehend graphics in the workplace. Many studies have analyzed the effects of background color when reading text, but few have studied its effects when reading graphics. OBJECTIVE: This study examines how different screen polarities and background colors can influence the reading and comprehension of graphics. PARTICIPANTS: 504 participants were selected by convenience sampling and divided into 14 groups. The experiment was performed in three parts. Parts 1 had 2 groups; Parts 2 had 6 groups; Parts 3 had 6 groups. Each group had 36 participants. METHODS: In each of the three parts of this study, a combination of black and white graphics was used as a background. Three experiments were performed. Color was the independent variable; accuracy in reading/comprehending graphics was the dependent variable. RESULTS: Experiment One showed that test participants performed better in positive (black on white) graphics test than in negative (white on black) graphics test on the computer screen. Experiment Two showed that screen background colors also significantly affect the accuracy of graphics reading/comprehension on the computer screen. Experiment Three showed that performance improved when the color of the computer screen polarity was adjusted. CONCLUSIONS: Screen polarity can affect the accuracy of graphics reading/comprehension; screen background color affects the accuracy of graphics reading/comprehension; adequate background color as a contrast increases experiments the accuracy of graphics reading/comprehension.